2012
DOI: 10.1038/jid.2011.271
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Psoriasis on Pregnancy Outcomes

Abstract: Psoriasis is an inflammatory disease that affects women in their reproductive years. Other similar diseases have been associated with adverse pregnancy outcomes. We sought to assess whether pregnant women with psoriasis are at higher risk of developing complications, such as preterm birth (PTB) and low birth weight (LBW). A retrospective cohort, performed at two large tertiary centers, evaluated the outcomes of 162 pregnancies in 122 women with psoriasis and 501 pregnancies in 290 women without psoriasis. Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 20 publications
6
74
0
11
Order By: Relevance
“…In a large Danish prospective cohort study of 100,418 pregnancies with a prevalence of psoriasis of 3 %, mild to moderate psoriasis was not found to be a risk factor for fetal death after the first trimester or for prolonged time to pregnancy [23]. This is also in line with Lima et al [24], who found no increased risk of spontaneous abortions in pregnant women with psoriasis.…”
Section: Pregnancy Outcomes With Psoriasissupporting
confidence: 68%
“…In a large Danish prospective cohort study of 100,418 pregnancies with a prevalence of psoriasis of 3 %, mild to moderate psoriasis was not found to be a risk factor for fetal death after the first trimester or for prolonged time to pregnancy [23]. This is also in line with Lima et al [24], who found no increased risk of spontaneous abortions in pregnant women with psoriasis.…”
Section: Pregnancy Outcomes With Psoriasissupporting
confidence: 68%
“…11 Another study found that women with psoriasis had increased odds for preterm birth and low birth weight, but the values were not statistically significant. 13 That study found similar rates of pre-eclampsia, caesarean delivery, and history of spontaneous abortions between pregnant women with psoriasis and controls. 13 These results must be interpreted with consideration of the comorbidities associated with psoriasis.…”
Section: Psoriasismentioning
confidence: 60%
“…13 That study found similar rates of pre-eclampsia, caesarean delivery, and history of spontaneous abortions between pregnant women with psoriasis and controls. 13 These results must be interpreted with consideration of the comorbidities associated with psoriasis.…”
Section: Psoriasismentioning
confidence: 60%
“…26 In a retrospective cohort study, psoriasis patients had a greater odds of a poor outcome composite (preterm birth and low birth weight), but not associated cesarean delivery, preeclampsia/eclampsia, or spontaneous abortion. 27 When comparing more than 3000 pregnancies in women with inflammatory skin disease to those without, there was no difference in incidence or outcome of pregnancy. 28 In 1 study, pregnant women with psoriasis (mean age, 32) were more likely to smoke, have a diagnosis of depression, and be overweight or obese before pregnancy, and were less likely to take preconceptional vitamin supplements, suggesting that the increased risk for adverse outcomes may be related to comorbidities and health behaviors in women with psoriasis.…”
Section: Pregnancymentioning
confidence: 96%